Minat ASN Pemerintah Provinsi Kepulauan Riau Dalam Pemenuhan Pengembangan Kompetensi - Destiana, Riska; Putra, Donie Tuah Fitriano (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
The ASN competency development paradigm underwent massive changes, most of which shifted towards learning methods that relied on technology. Meanwhile, most of the ASN in the Riau Islands Provincial Government are generation X, which in fact some of them are still experiencing difficulties adapting to working with technology. This article will discuss the interest of ASN Riau Islands Provincial Government in fulfilling competency development. This study uses a quantitative and qualitative approach. ASN interest data was taken from webinar membership data held by BPSDM Riau Islands Province, and analyzed using generation theory. The ASN generation at a younger age tends to have an interest in competency development models that are not bound by traditional class methods, can adapt to the use of technology, wants a collaborative way of learning. The way of learning for each generation should be taken into consideration for policy making in the preparation of competency development plans and models.